Application of Maqasid Approach of Malaysia into Political Participation Systems of Sri Lankan Muslims - RISHARD, NAJIMUDEEN MOHAMED (2018)
Sri Lankan Muslims have been involving in direct politics for more than one century. Muslim politicians had always preferred to engage with Sinhalese national parties rather than form a Muslim ethno-centric party.